2017
DOI: 10.7717/peerj.4170
|View full text |Cite
|
Sign up to set email alerts
|

Arbutin increases Caenorhabditis elegans longevity and stress resistance

Abstract: Arbutin (p-hydroxyphenyl-β-D-glucopyranoside), a well-known tyrosinase inhibitor, has been widely used as a cosmetic whitening agent. Although its natural role is to scavenge free radicals within cells, it has also exhibited useful activities for the treatment of diuresis, bacterial infections and cancer, as well as anti-inflammatory and anti-tussive activities. Because function of free radical scavenging is also related to antioxidant and the effects of arbutin on longevity and stress resistance in animals ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The feeding program for the stress resistance assay was the same as that for the lifespan assay, and the conditions were identical to those in a previous study (Zhou et al, 2017). Wild-type nematodes at the L4 stage were incubated with 0.1 mM didymin for 48 and transferred to new plates without didymin, immediately followed by three kinds of stressors.…”
Section: Methodsmentioning
confidence: 99%
“…The feeding program for the stress resistance assay was the same as that for the lifespan assay, and the conditions were identical to those in a previous study (Zhou et al, 2017). Wild-type nematodes at the L4 stage were incubated with 0.1 mM didymin for 48 and transferred to new plates without didymin, immediately followed by three kinds of stressors.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular ROS were measured in transgenic C. elegans strain CL4176, using the 2′,7′-dichlorofluorescein diacetate (H2DCF-DA) method [ 4 , 42 , 43 ]. Briefly, synchronization of worms was performed on fresh NGM dishes with or without MCCP and were incubated at 16 °C (permissive temperature) for 48 h. To initiate amyloid-induced progressive paralysis, the worms were transferred from 16 °C to 25 °C for cultivation.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with lowbush cranberry and essential oil alloaromadendrene failed to increase the lifespan of daf ‐16 mutants, indicating that a DAF‐16/FOXO transcription factor is required but not Alaskan blueberry (Scerbak, Vayndorf, Hernandez, McGill, & Taylor, 2018; Yu et al., 2014). The protective effect of low‐concentration arbutin against aging and oxidative stress was also dependent on DAF‐16, indicating that arbutin‐treated C. elegans exhibited increased resistance to stress (Zhou et al., 2017). Blueberry extract (BE) exerted no significant effect on the lifespan of daf‐16 mutants, and the increased genetic expression level suggested that BE could promote daf‐16 expression and then increase downstream sod‐3 expression to extend lifespan and stress resistance (Wang, Liu, Li, & Liu, 2018).…”
Section: Caenorhabditis Elegans As a Powerful Model For Antiaging Evamentioning
confidence: 99%
“…Biphasic dose responses of the hormetic type are common effects of chemicals from foodstuff. For instance, curcumin (Scuto et al., 2019), olive polyphenols (Di Rosa et al., 2020), green tea catechins (Miquel et al., 2018), and arbutin (Zhou et al., 2017) shown to be biologically active, are harmful in high doses and have contributed to the progresses of some diseases. Scientific research has concluded that the quantitative features of compounds have an important implication in research results and that it is not reliable to determine the safety and risk of the substances without the dosage.…”
Section: Caenorhabditis Elegans As a Powerful Model For Antiaging Evamentioning
confidence: 99%